ANALISIS PENGARUH SUKU BUNGA KREDIT DAN KRISIS EKONOMI TERHADAP PENANAMAN MODAL DALAM NEGERI DI INDONESIA TAHUN 1990-2010 - Alfarisi, Salman (Jurnal Ekonomi Pembangunan, 2011)
This study aims to determine the development of  domestic direct investment (DDI) with lending rates level and to determine the effect of lending rates and economic crisis on domestic direct investment (DDI) in Indonesia in 1990-2010. Based on the result of regression analysis found that the coefficient value of determination (R2) is 0.499. It means the ability of the independent variables consist of lending rates level and economic crisis which is able to explain 49 % of the dependent variable that is domestic direct investment (DDI). From the t test results obtained the level of lending rates have a significant influence on domestic direct investment (DDI) this is proved by t count > t table is amounted to -4.235 > 2.101. On the other hand, the economic crisis has the value t count is 2.432, therefore, the economic crisis also significantly influence the domestic direct investment (DDI). Obtained from the F test that both of lending rates level and economic crisis significantly influence on domestic direct investment (DDI). This is proved by the value of F count (8.972) > F table (3.55).